1999
DOI: 10.1097/00006842-199911000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Zazen and Cardiac Variability

Abstract: These data are consistent with the theory that increased oscillation amplitude during slow breathing is caused by resonance between cardiac variability caused by respiration and that produced by physiological processes underlying slower rhythms. The rhythm irregularities during inhalation may be related to inhibition of vagal modulation during the cardioacceleratory phase. It is not known whether they reflect cardiopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
92
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 38 publications
15
92
0
2
Order By: Relevance
“…As frequency of daily practice varies between meditation practitioners, using the total number of years of practice is not a sensitive metric of experience. One effect of regular meditation practice is a significant drop in respiration rate during formal practice [7,8]. We therefore tested whether changes in respiration rate between rest and meditation could serve as an objective measure of meditation experience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As frequency of daily practice varies between meditation practitioners, using the total number of years of practice is not a sensitive metric of experience. One effect of regular meditation practice is a significant drop in respiration rate during formal practice [7,8]. We therefore tested whether changes in respiration rate between rest and meditation could serve as an objective measure of meditation experience.…”
Section: Resultsmentioning
confidence: 99%
“…Other forms of yoga and meditation will likely have a similar impact on cortical structure, although each tradition would be expected to have a slightly different pattern of cortical thickening based on the specific mental exercises involved [7,8,25]. Although numerous studies have shown that indices of cortical size can decrease as a result of aging and pathology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…At approximately 6 breaths per minute or 0.1 Hz, RSA synchronizes with inherent low frequency variability leading to significantly increased amplitude of heart rate variability. [15][16][17][18][19] ( Figure 1) This is the same physiology that occurs during biofeedback training to increase heart rate variability. 20 A rate of breathing of 6 breaths per minute or 0.1 Hz also coincides with and augments the intrinsic blood pressure variation known as the Mayer wave 21 , a complex phenomenon of autonomic activity that results in an approximately 10 second cycle (0.1 Hz or 6 per minute) of blood pressure.…”
mentioning
confidence: 98%
“…One study in which HRV parameters were measured while participants breathed at specified rates found that total HRV amplitude peaked at four breaths per minute, as did low-frequency HRV amplitude (Song & Lehrer, 2003). This is also within the breathing frequency range utilized by Zen monks for the practice of "tanden breathing," during which their HRV increases in the low-frequency band, and decreases in the high-frequency band (Lehrer, Sasaki, & Saito, 1999). The NFB+HRV protocol utilized in the current study combined biofeedback to encourage slow, deep breathing (at 6-8 breaths per minute) with HRV biofeedback to up-train the %LF band.…”
Section: Discussionmentioning
confidence: 81%